RE-EVALUATING YORUBA MARKET COSMOLOGY AND IMPACT ON MARKET DEVELOPMENT - OLAYINKA ALIU; SOLANKE STEPHEN O. (International Studies Journal)
In the lives of the Yoruba, a major ethnic group in Western Nigeria, the market remains central. Asa society whose pre-occupation is principally agricultural, all processes in the development of traditional markets are important because they occupy vital positions in the people’s economic life. The use of foundation rituals is an important process in the establishment of traditional markets in Yorubaland. Hence, this study examines the place of this inherent cosmological tasks in the establishment of traditional markets, effects and implications for the socio-economic development of the people. It was discovered that there are the establishment of new and modern markets without any foundational rituals withthe markets in one way or the other having continuation problems. This research examined the effects of the presence (or absence) of cosmological implantation towards the longevity of markets in the Yoruba world and the people. Foundationrituals and sacrifices in the establishment of the markets, as done in the past, are equallyimperative for the longevity in the life-span of the markets and socio-economic community where the markets are sited.Methodology usedare historical, oral interviews, secondary sources and field work.